Knowledge sharing behaviour among sri lankan public university undergraduates: An application and extension of the theory of planned behaviour - Sasiraj, S.; Umanakenan, R.; Achchuthan, S. (University of Jaffna, 2020)
This study investigates the antecedents of knowledge sharing behaviour among the undergraduates in an emerging country context, using widely accepted socio psychological theory. 251 usable responses were collected using questionnaire surveys from one of the State University in Sri Lanka. Multiple regression analysis using SPSS was employed for analyses. The findings showed that attitudes towards knowledge sharing, subjective norms and perceived behavioural control are positively associated with knowledge sharing intention. Further, knowledge sharing intention and level of Information Communication Technology (ICT) usage enhance the knowledge sharing behaviour. This study contributes to the theory of planned behaviour in knowledge sharing context. Practically, this study provides several recommendations to enhance knowledge sharing behaviours.
Keywords: Knowledge sharing behaviour; Knowledge sharing intention; Theory of planned behaviour and undergraduates